Wideband optical detector of ultrasound for medical imaging applications - Rosenthal, Amir; Kellnberger, Stephan; Omar, Murad; Razansky, Daniel; Ntziachristos, Vasilis (Journal of Visualized Experiments, 2014)
Optical sensors of ultrasound are a promising alternative to piezoelectric techniques, as has been recently demonstrated in the field of optoacoustic imaging. In medical applications, one of the major limitations of optical sensing technology is its susceptibility to environmental conditions, e.g. changes in pressure and temperature, which may saturate the detection. Additionally, the clinical environment often imposes stringent limits on the size and robustness of the sensor. In this work, the combination of pulse interferometry and fiber-based optical sensing is demonstrated for ultrasound detection. Pulse interferometry enables robust performance of the readout system in the presence of rapid variations in the environmental conditions, whereas the use of all-fiber technology leads to a mechanically flexible sensing element compatible with highly demanding medical applications such as intravascular imaging. In order to achieve a short sensor length, a pi-phase-shifted fiber Bragg grating is used, which acts as a resonator trapping light over an effective length of 350 μm. To enable high bandwidth, the sensor is used for sideway detection of ultrasound, which is highly beneficial in circumferential imaging geometries such as intravascular imaging. An optoacoustic imaging setup is used to determine the response of the sensor for acoustic point sources at different positions.
CRIS-Team Scopus Importer:2023-03-08
Keywords: Bioengineering; Fiber Bragg gratings; Interferometry; Issue 87; Optical fibers; Optical sensors; Optoacoustic imaging; Photoacoustic imaging; Pulse interferometry; Ultrasound